FAKTOR HARGA, PENDAPATAN, DAN TANGGUNGAN KELUARGA YANG BERPENGARUH TERHADAP PERMINTAAN DAGING SAPI DI PASAR TRADISIONAL KOTA MAKASSAR - Astaman, Putra; Hikmah, Aulia Nurul; Siregar, Ahmad Ramadhan; Dassir, Muhammad; Darwis, Muhammad; Hariyadi, Hariyadi; Yousof, Sadam Suliman Mohamed (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
Animal husbandry is a subsector that is fully responsible for meeting the nutritional needs of animals. Beef contains nutrients that are beneficial to the human body. However, Indonesian consumption is still far below the standard of about 2.2 kg/capita/year. The purpose of this study is to analyze the effect of price, income, and family dependents on beef demand in Makassar City. The research method uses a descriptive quantitative approach with the help of a questionnaire, the data is processed by multiple regression analysis using SPSS. The results showed a significant effect partially, the factors of price, income and number of family dependents had a real influence on beef demand. In the simultaneous test, the factors of price, income and number of family dependents have a significant influence on the total demand for beef in the Terong market in Makassar city.